Origin of Ising magnetism in Ca3Co2O6 unveiled by orbital imaging - Brett Leedahl (Nature Portfolio, 2019)
Ca$${}_{3}$$ 3 Co$${}_{2}$$ 2 O$${}_{6}$$ 6 has an unconventional magnetic structure displaying quantum tunnelling phenomena in its magnetization. Here, the authors use s-core-level non-resonant inelastic X-ray scattering to image the atomic Co 3d orbital that is responsible for the Ising magnetism in this system.